Biology of Sex Differences - Reckelhoff, Jane; Arnold, Arthur
Unlike any other scientific journal, Biology of Sex Differences focuses on sex differences in physiology, behavior, and disease, from molecules to phenotypes, and incorporates basic and clinical research. The journal aims to improve understanding of basic principles and foster development of therapeutic and diagnostic tools that are specific for sex differences. This open access journal is the highly respected official journal of the Organization for the Study of Sex Differences, and is co-published by the Society for Women’s Health Research.   Topical areas include, but are not limited to sex differences in: genomics the microbiome epigenetics molecular and cell biology tissue biology physiology interaction of tissue systems, in any system including adipose, behavioral, cardiovascular, immune, muscular, neural, renal, and skeletal clinical studies bearing on sex differences in disease or response to therapy For further information about the material covered by Biology of Sex Differences, please see our "Submission Guidelines" below and to view details of our Editorial Board members, please visit the  "Editorial Board" page.